2019
DOI: 10.1111/1440-1681.13147
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miR‐146a, miR‐34a and miR‐375 in type 2 diabetes patients, pre‐diabetic and normal‐glycaemic individuals in relation to β‐cell function, insulin resistance and metabolic parameters

Abstract: The pathogenesis of type 2 diabetes (T2D) is associated with a progressive loss of pancreatic β-cell mass. It is known that miR-146a, miR-34a, and miR-375 are involved in β-cell functionality. In this work, we evaluated the levels of these miRNAs in normal-glycaemic individuals, pre-diabetic, and T2D patients in relation to β-cell functionality, insulin resistance, and metabolic parameters. The relative expression of the miRNAs was evaluated in serum samples by real-time polymerase chain reaction. In a princip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 34 publications
2
20
1
Order By: Relevance
“…Also, the up regulation of MicroRNAs and attenuated the expression of pro-inflammatory cytokines was confirmed by treating cells with mango extracting rat 21 . Moreover, in context to placebo group, we indicated that the expression of miR-146a was augmented during the intervention and associated with raised IL-6 and MDA which is consistent with previous studies 18 . Also in a study conducted by 22 , a positive correlation was observed between miR-146a levels and concentration of inflammatory mediators, whereas, elevated miR-146a inhibited the production of IL-6 and IL-21 in T cells.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Also, the up regulation of MicroRNAs and attenuated the expression of pro-inflammatory cytokines was confirmed by treating cells with mango extracting rat 21 . Moreover, in context to placebo group, we indicated that the expression of miR-146a was augmented during the intervention and associated with raised IL-6 and MDA which is consistent with previous studies 18 . Also in a study conducted by 22 , a positive correlation was observed between miR-146a levels and concentration of inflammatory mediators, whereas, elevated miR-146a inhibited the production of IL-6 and IL-21 in T cells.…”
Section: Discussionsupporting
confidence: 91%
“…This specific effect of AST on miR-146a expression behavior might be the consequence of a pro-inflammatory component of the T2D. In this regard, the results from the other studies showed that miR-146a relative expression was associated with an inflammatory marker in the T2D patients 18 . Also, the modulatory effect of some antioxidants on circulating MicroRNAs was examined in previous studies and suggested to consider as a novel therapeutic target in disease management in many literature 19,20 .…”
Section: Discussionmentioning
confidence: 86%
“…There is growing evidence that the relative expression of miR-146a is associated with inflammatory markers and it is described as a regulating biomarker of inflammation. 22 Moreover recent studies found several numbers of circulating cytokines and miRNAs deregulated in subjects with T2DM. Specifically, cytokines IL-6, as well as miR126 and miR-146a, altered across the diabetic spectrum, and they also related to pancreatic β cell function and glycaemic control.…”
Section: Discussionmentioning
confidence: 99%
“…25 Concerning the placebo group, we indicated that the expression of miR-146a was augmented during the study and associated with raised IL-6 and MDA, which is consistent with previous studies. 22 The observed high levels of plasma MDA and IL-6 result in the oxidation of glucose and generation of free radicals in diabetic patients. 26 The role of elevated miR-146a in the modulation of IL-6 and interleukin 21 (IL-21) production in T cells has also been well documented previously.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of miR-375 are also established in the islet of T2D patients in comparison with healthy subjects and an animal model of obesity and insulin resistance. Similarly, human blood-based higher expression of miR-375 was detected in T2D patients [ 45 ]. Several reports suggest the potential involvement of epigenetic mechanisms in developing T2D as a crucial boundary between the effects of genetic predisposition and environmental effects [ 46 ].…”
Section: Discussionmentioning
confidence: 99%